Exploring the Role of Artificial Intelligence, Business Agility, and Business Model Innovation in Enhancing Culinary MSMEs Performance - Romindo Megawati Pasaribu; Hanna Meilani Damanik; Trimelda Mei Liana Sitorus (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study aims to identify the factors influencing the performance of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector, with a particular focus on their capabilities in artificial intelligence (AI). The research examines business model innovation as a mediating factor and business agility as a moderating factor.Method: The research was conducted in Medan, targeting culinary entrepreneurs with a sample size of 165 respondents. Hypothesis testing was performed using PLS-SEM.Result: The results indicate that AI capabilities and business model innovation have a positive and significant impact on the business performance of culinary MSMEs in Medan. Mediation analysis reveals that business model innovation effectively mediates the relationship between AI capabilities and the performance of culinary MSMEs. However, moderation analysis shows that business agility does not strengthen the impact of AI capabilities and business model innovation on business performance.Practical Implications for Economic Growth and Development: This study emphasizes the significance of artificial intelligence, business agility, and business model innovation in enhancing the performance of MSMEs within the culinary sector. Adopting AI, improving business agility, and promoting business model innovation can enhance MSMEs' performance and contribute to digital economic growth.Originality/Value: This study evaluates AI capacity through mediation and moderation approaches based on the Resource-Based View (RBV) theory. It explores how AI capabilities, business agility, and business model innovation can improve MSME performance, an area that remains underexplored in developing countries such as Indonesia.